Inclusion body myositis: an underdiagnosed condition?. Issue 2 (February 1993) - Hopkinson, N D; Hunt, C; Powell, R J; Lowe, J
Abstract : Inclusion body myositis is an increasingly recognised form of inflammatory myopathy with characteristic clinical and histopathological features which has seldom been reported in the United Kingdom. This paper presents the clinicopathological features of a series of patients diagnosed in Nottingham from 1986 to 1990. During this period, 1319 muscle biopsy samples were processed by this laboratory and rimmed vacuoles were seen in 17 patients. Eleven patients had definite or probable inclusion body myositis according to published criteria. The mean age of the group was 69.4 years with a male to female ratio of 8:3. Typical clinical features were a slowly progressive painless, proximal lower limb weakness, with muscle wasting and early loss of reflexes. The median duration of illness from first symptom to presentation was five years (range 2-18 years). Falls were a prominent symptom in six patients and distal weakness occurred in nine patients. Creatine kinase was increased in 10 patients but only one had a level > 1000 IU/l; the erythrocyte sedimentation rate was normal in five patients. Treatment with steroids or cytotoxic drugs, or both, did not prevent disease progression. It is confirmed that inclusion body myositis is a distinct cause of inflammatory myopathy which is probably underdiagnosed in the United Kingdom. Clinically, it should be suspected in older patients presenting with muscle weakness of insidious onset. Pathologically, a careful search should be made for rimmed vacuoles and inflammation; ultrastructurally, the presence of inclusions will confirm the diagnosis.